Prenatal care in Quixadá-CE according to SISPRENATAL's process indicators - Grangeiro, Gisele Ribeiro; Diógenes, Maria Albertina Rocha; Moura, Escolástica Rejane Ferreira (Revista da Escola de Enfermagem da USP, 2008)
This is a descriptive, documental survey aimed at analyzing the process indicators of the Prenatal Information System (Sisprenatal) in the municipality of Quixadá, State of Ceará. The records of 1,544 pregnant women from 2001 through 2004 were studied. Data were collected from February through April, 2005 in Sisprenatal, located in the Epidemiology sector of the local Health Secretary. The results were presented in a single chart containing absolute and relative frequency. They were analyzed in the light of current literature and the authors' experience. In the period was verified a growing percentage of pregnant women with indicators of at least six appointments, all the basic exams, anti-HIV test, antitetanic immunization and puerperal consultation, from zero percent (2001), to 2.6% (2002), to 5.68% (2003) to 21.11% (2004). Thus it is necessary to improve the use of the system, as well as the systematic reading of the process indicators, in order to obtain subsidies for the enhancement of the quality of prenatal assistance.